Exploring high-performance green innovation in China’s logistics companies: a TOE framework based on fsQCA - Li, Shuhua; Zhu, Jiaqi; Chen, Peixian; Li, Zhao; Liao, Caisheng; Feng, Wei (Frontiers in Environmental Science, 2025)
In recent years, the Chinese logistics industry has experienced rapid development. However, this expansion is accompanied by significant challenges, including high energy consumption and greenhouse gas emissions. Despite these issues, the key factors improving logistics firms’ green innovation remain insufficiently explored. This study fills this gap by utilizing the Technology-Organization-Environment (TOE) framework as a foundation, introducing a comprehensive analytical model to investigate the dynamics of green innovation in logistics companies. Moreover, after employing fuzzy-set Qualitative Comparative Analysis (fsQCA) with data from 83 logistics firms in China, the research examines the complex interplay between technological, organizational, and environmental factors and their strategic influence on green innovation performance. The study yields three pivotal findings: (1) High-level green innovation performance is not predicated on a single factor. (2) Logistics firms can attain superior green innovation performance through two driving paths: Core competencies and market pressure driven as well as technological innovation and government subsidies driven. (3) The analysis of low-level green innovation performance reveals that four distinct paths can culminate in this outcome, with the lack of digitalization, organizational slack, and market pressure being instrumental in this result. These insights highlight the principles of “multiple concurrency” and “different paths leading to the same goal,” significantly enhancing the current knowledge base on green innovation performance and deepening our understanding of the multifaceted drivers of high-performance green innovation in logistics companies. Moreover, the discoveries offer practical implications for firms and the government to improve green innovation performance within the logistics industry.